EFFECT OF REEDBED SYSTEM ON GREY WATER TREATMENT - H. R. Mangio; M. S. Mirjat; M. A. Talpur; I. Rajpar; A. Sarki (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2016)
The cogency of reedbed system was evaluated for the treatment of grey water using three grass species including reed grass (Phragmites karka), reed mace (Typha elephantina) and large sedge grass (Cyperus iria) for consecutive two years (2013 and 2014). The reedbed system was installed at the residential colony of Sindh Agriculture University, Tandojam, Sindh, Pakistan. The statistical analysis of the data indicated that the effect of three grass species on the removal of contaminants from grey water was significant (P < 0.05); while the effect of years on removal was non-significant (P > 0.05). The average removal (%) of BOD, COD, pH, TSS and turbidity from grey water passing through Phragmites karka, Typha elephantina and Cyperus iria grass species was 60.18±11.34, 38.30±8.10 and 26.09±4.75%; 45.10±4.69, 36.73±8.84 and 35.90±5.84%; 5.63±2.12, 4.75±1.99 and 4.31±2.29%; 45.86±10.51, 37.99± 10.35 and 31.44±8.92%; 86.10±4.82, 81.66±16.83 and 86.11±4.88%, respectively. The maximum removal of BOD, COD, pH, TSS and turbidity was found under Phragmites karka, followed by Typha elephantina and minimum removal of all parameters was recorded under Cyperus iria. Hence, Phragmites karka proved to be more effective reed grass for maximum removal of contaminants from grey water making it more useful for crop production compared to other two grass species.